2004
DOI: 10.1097/01.don.0000125880.11248.74
|View full text |Cite
|
Sign up to set email alerts
|

Cold Testing Through Full-Coverage Restorations

Abstract: Endodontic diagnosis often requires thermal testing through porcelain fused-to-metal (PFM) and all-ceramic restorations. The purpose of this study was to measure and compare the temperature change during thermal testing by three commonly used methods occurring at the pulp-dentin junction (PDJ) of nonrestored teeth and teeth restored with full coverage restorations made of PFM, all-porcelain, or gold. The methods used to produce a thermal change were (a) an ice stick, (b) 1,1,1,2-tetrafluoroethane (TFE), and (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 16 publications
1
31
1
1
Order By: Relevance
“…In vitro studies (6,12) have reported a faster rate of temperature change produced by refrigerant sprays than the rate with CO 2 , but without superior accuracy, and the current study had similar findings with regards to accuracy. Perhaps the warmer oral environment might play a more significant effect on test outcome than was originally suggested by Miller et al (13).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In vitro studies (6,12) have reported a faster rate of temperature change produced by refrigerant sprays than the rate with CO 2 , but without superior accuracy, and the current study had similar findings with regards to accuracy. Perhaps the warmer oral environment might play a more significant effect on test outcome than was originally suggested by Miller et al (13).…”
Section: Discussionmentioning
confidence: 84%
“…DDM has decreased in popularity because of environmental concerns (13), and it has been replaced by other gases such as the mixture of propane, butane, and isobutane (Endo Frost [EF]; Roeko, Langenau, Germany). Concerns have been raised about possible damaging effects of cold testing agents to teeth, but studies have shown that they are safe (14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…It is an efficient method to test multiple teeth without moving away from the mouth, and although initial set-up costs may be high, there is evidence that CO 2 may be more cost effective in the long term. Cold sprays are perceived to be more convenient, easily stored and relatively inexpensive to use, which may explain their more frequent use in private practice (13,(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…TFE tekniği kuru buz tekniğinden daha hızlı ve etkilidir. 17,25 PBM'nin ticari ismi Endo-Frost (-50 ˚C) dur. Genellikle %30-50 proban, %30-50 bütan, %10-20 izobütan içerir.…”
Section: Buz çUbuklarıunclassified